Exploring education leaders’ perceptions of the effectiveness of socio-religious organisations in higher education funding in Cross River State, Nigeria - Onya, Osim Rosemary; Chukwudi, Uzoigwe Michael; Godwin, Akeke, Mercy Nkiruka; Okpa, Ovat, Egbe; Ugah, Uguma, Vincent; Ekpo, Alice Mbang (Nurture, 2024)
Purpose: This study examines education leaders’ perceptions of the effectiveness of socio-religious organizations in higher education funding in Cross River State, Nigeria, focusing on the University of Calabar and Cross River State University. Design/Methodology/Approach: A survey consisting of 34 items was developed, validated, and administered to 146 educational leaders from the two public universities in Cross River State. The survey aimed to gather their views on the effectiveness of socio-religious organizations in funding higher education. Findings: The results indicate that while some socio-religious organizations are perceived to contribute to a vibrant and prosperous school community, they have not fully addressed the economic opportunities, skills, and knowledge needed for student workforce success. Gender and experience did not significantly relate to socio-religious organizations’ funding in higher education. Conclusion: This study explores education leaders’ perspectives on the effectiveness of socio-religious organizations in funding higher education and suggests that addressing differences among education leaders can enhance learning experiences. Research Limitations and Implications: The focus on education leaders’ perspectives, the specific geographical context of Cross River State, Nigeria, and the reliance on self-reported survey data, which may be subject to response biases; therefore, caution should be exercised in generalizing the findings to other contexts. Practical Implications: The effectiveness of higher education funding depends on various factors, including institutional context, funding nature, and the values of the funding organization. Contributions to Literature: Socio-religious organizations can contribute to higher education funding through scholarships, grants, and donations to institutions, highlighting the diverse ways in which they can support educational advancement.